The Effect of Electronic Word Of Mouth (E-Wom) on Instagram Social Media on Interest in Visiting Followers @Rummahgoa - Kurniawan, Farras Ulfiyah; Yasya, Wichitra (Social Sciences Journal, 2025)
The phenomenon of high interaction among social media users significantly influences the interest in visiting certain destinations. This study aims to measure the influence of Electronic Word of Mouth (E-WOM) on Instagram social media on the interest in visiting followers of the @rummahgoa account. This study uses a quantitative approach with a survey method, involving respondents who are followers of the @rummahgoa Instagram account. Data were collected through questionnaires distributed online with 100 respondents and analyzed using descriptive statistical tests, simple linear regression, and hypothesis testing. The results of the simple linear regression test show that the E-WOM variable contributes 33% to the variation in visiting interest (Y), while the rest is influenced by other factors such as location, price, and direct experience of visitors. A positive regression coefficient indicates that an increase in E-WOM by one unit will increase visiting interest by 0.321. The results of the t-test show a significant relationship between the two variables with a calculated t value of 6.949 > t table = 1.984 and a significance level of 0.000 < 0.05. In conclusion, E-WOM on Instagram social media is an effective marketing strategy in increasing visitor interest, especially in the context of culinary destination promotion. This study provides practical insights for business actors to utilize social media as a digital marketing tool, especially by maximizing captivating and interactive content.